2013
DOI: 10.1016/j.cell.2013.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Inhibits Autophagy and Promotes Growth by Inducing the SAM-Responsive Methylation of PP2A

Abstract: Summary Autophagy is a process of cellular self-digestion induced by various forms of starvation. The mechanisms by which metabolic deficiencies are sensed by a cell to regulate autophagy remain unclear. While nitrogen deficit is a common trigger, yeast cells induce autophagy upon switch from a rich to minimal media without nitrogen starvation. We show that the amino acid methionine is sufficient to inhibit such non-nitrogen starvation (NNS)-induced autophagy. Methionine boosts synthesis of the methyl donor, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
265
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(279 citation statements)
references
References 51 publications
13
265
0
1
Order By: Relevance
“…Presently, little is known of the regulation of S-adenosyl methionine synthetase activity and the control of SAM uptake in the brain. In yeast, a mechanism for sensing SAM levels was revealed that would determine metabolic processes underlying growth (22). Possibly, the mammalian brain also has a mechanism for monitoring SAM levels that determines the neuronal response to environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, little is known of the regulation of S-adenosyl methionine synthetase activity and the control of SAM uptake in the brain. In yeast, a mechanism for sensing SAM levels was revealed that would determine metabolic processes underlying growth (22). Possibly, the mammalian brain also has a mechanism for monitoring SAM levels that determines the neuronal response to environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether the inhibitory action of SAM on c-Fos and Egr-1 induction was due to an effect on H3S10p-K14ac formation. For instance, SAM has been shown to increase protein phosphatase activity via methylation (22). Treating rats with SAM before FS however did not affect the formation of H3S10p-K14ac in DG granule neurons (Fig.…”
Section: Sam Impairs Consolidation Of Fs-induced Behavioral Responsesmentioning
confidence: 99%
“…Methionine and S-adenosylmethionine (SAM) are essential metabolites that have gained considerable scientific attention because of their recently discovered roles as sentinel metabolites in the control of the eukaryotic cell cycle (10), autophagy (11), and differentiation of human pluripotent stem cells (12). Methionine takes a leading role in translation initiation (13) and is the precursor of SAM, a cofactor for one-carbon metabolism, the process responsible for the methylation of DNA, RNA, proteins, and lipids by SAM-dependent methyltransferases (14).…”
mentioning
confidence: 99%
“…The origin of the delay upon methionine removal may therefore also be related to a general growth rate and stress-related signalling mechanism. The molecular details of this global response are currently subject to active research 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to methionine storage capacity, the regulatory roles of methionine and SAM can also contribute to the observed transcription response delay. Reduction of the intracellular methionine level is perceived by yeast and initiates several stress response mechanisms, such as a growth stop and, eventually, autophagy 54,55 . However, methionine has a particularly complicated role in cell survival and growth control 56 .…”
Section: Discussionmentioning
confidence: 99%